Strengthening the Healthy Living Society Movement (GERMAS) during the Covid Pandemic 19 - Rizal Sanif (Conferences of Medical Sciences Dies Natalis, 2020)
Health problems in Indonesia are very serious challenges. The main problem is that there is a triple burden or three important health problems related to the eradication of infectious diseases, an increase in cases of non-communicable diseases and the re-emergence of types of diseases that should have been successfully resolved. Infectious diseases such as diarrhea, tuberculosis and dengue fever were the most common health cases; now there has been a marked change in the number of cases of non-communicable diseases such as diabetes, cancer and coronary heart disease. The Government of the Republic of Indonesia at the Ministry of Health in 2017 launched GERMAS or Healthy Living Community Movement. GERMAS is a movement that aims to promote a culture of healthy living and leave unhealthy habits and behavior of society. The GERMAS action was also followed by promoting hygiene and healthy living habits and support for community-based infrastructure programs. This program has several focuses, such as building access to meet drinking water needs, community health installations and the construction of habitable settlements. The three of them are the basic infrastructure that is the foundation of the healthy life movement.